Efficacy and Safety of Transdermal Buprenorphine versus Oral Tramadol/Acetaminophen in Patients with Persistent Postoperative Pain after Spinal Surgery. (13th September 2017) - Lee, Jae Hyup; Kim, Jin-Hyok; Kim, Jin-Hwan; Kim, Hak-Sun; Min, Woo-Kie; Park, Ye-Soo; Lee, Kyu-Yeol; Lee, Jung-Hee
Abstract : Purpose . Control of persistent pain following spinal surgery is an unmet clinical need. This study compared the efficacy and safety of buprenorphine transdermal system (BTDS) to oral tramadol/acetaminophen (TA) in Korean patients with persistent, moderate pain following spinal surgery. Methods . Open-label, interventional, randomized multicenter study. Adults with persistent postoperative pain (Numeric Rating Scale [NRS] ≥ 4 at 14–90 days postsurgery) were enrolled. Patients received once-weekly BTDS (n = 47 ; 5  μ g/h titrated to 20  μ g/h) or twice-daily TA (n = 40 ; tramadol 37.5 mg/acetaminophen 325 mg, one tablet titrated to 4 tablets) for 6 weeks. The study compared pain reduction with BTDS versus TA at week 6. Quality of life (QoL), treatment satisfaction, medication compliance, and adverse events (AEs) were assessed. Findings . At week 6, both groups reported significant pain reduction (mean NRS change: BTDS −2.02; TA −2.76, bothP < 0.0001 ) and improved QoL (mean EQ-5D index change: BTDS 0.10; TA 0.19, bothP < 0.05 ). The BTDS group achieved better medication compliance (97.8% versus 91.0%). Incidence of AEs (26.1% versus 20.0%) and adverse drug reactions (20.3% versus 16.9%) were comparable between groups. Implications . For patients with persistent pain following spinal surgery, BTDS is an alternative to TA for reducing pain and supports medication compliance. This trial is registered with Clinicaltrials.gov:NCT01983111 .